Geomorphologycal Study for Flood and Mass Movement Occurrence at Parang Sub Village, Paranggupito District, Wonogiri Regency - Sunarhadi, Muhammad Amin (Universitas Muhammadiyah Surakarta, 2001)
The aim of this study are knowing factors that impacts to flood and mass movement hazard at karst region. Area of this study are covering Parang Sub Village, Ngasem, Paranggupito District, Wonogiri Regency. To achieve this objective, geomorphic approaches (static, as well as dynamic environmental geomorphology) were analyzed, using survey and secondary data collection. Results from this study are describe that Parang is a karst depression and had water accumulated from Parang boundaries area as upper landform. Mass movement at study area is caused by saturation of soil by water after rainfall. Supported by steep slope impact sliding mass movement. Based on the priority, to change the water running direction and will not concentrate to Parang Depresion, there are need the water-massbank stability. This bank will prevent the soil mass to stable.